Cover Picture: Influence of Soil Variation on Diosgenin Content Profile in Costus speciosus from Indo‐Gangetic Plains (Chem. Biodiversity 6/2021). Issue 6 (26th May 2021) - Rawat, Poonam; Kumar, Manish; Srivastava, Akanksha; Kumar, Bhanu; Misra, Ankita; Pratap Singh, Satyendra; Srivastava, Sharad
Abstract : Cover Picture . Diosgenin is a commercially viable aglycone molecule and is therapeutically valuable as it is key precursor in corticosteroid synthesis at industrial scale. The preferred natural source of Diosgenin, worldwide is Dioscorea spp., and the species is continuously facing threat of biodiversity loss due to over exploitation. Alternatively, the yield of diosgenin from natural resources varies significantly from one population to other depending upon the phytogeographical determinants. In the present context, an alternative species C. speciosus as a source of diosgenin was explored and a comprehensive analysis of variation in its diosgenin content (rhizomes) was carried out in the germplasm(s) collected from different locations of the Indo‐Gangetic Plain (India). In due course of study, a systematic collection strategy was adopted to cover the maximum possible variation existing in the natural population of species, its growth stage, season of collection etc . Further the extraction process also plays a very crucial role to set the diosgenin in free form (therapeutically active form) for quantification. The effect of soil micro/macronutrients on the diosgenin content has been established. The chemotaxonomic study on C. speciosus will result in identification of elite (diosgenin rich) germplasm(s) of species and its commercial cultivation at site specific locations will lead to the identification of good quality planting materials. This will ultimately ensure the sustainable availability of good quality raw material to the herbal drug industries and also decrease the burden on natural resources. Moreover, the development of suitable agro techniques for elite germplasm(s) of C. speciosus will uplift the availability of raw material and socio‐economic upliftment of local inhabitants in area's having similar phytogeographical location, as reported by Sharad Srivastava et al . in their full paper at 10.1002/cbdv.202000977 .